EFEKTIFITAS PENGGUNAAN BAHASA INDONESIA PADA LAPORAN KEUANGAN PT. CAHAYA BINTANG MEDAN Tbk - Nur Azizaini Zhaharah; Narach Larasati Nasution; Anggie Pricyla Sianturi; Imelda Malona Tarigan; Dinda Dwi Aprillia; Ayu Nadira Wulandari (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Financial reports serve not only as an internal communication tool, but also as a medium of transparency for stakeholders, both domestic and international. The use of Bahasa Indonesia is expected to improve understanding and accessibility for local stakeholders, but there are challenges in translating accounting language that is often better known in English. This research uses a qualitative approach by analyzing the financial statements of PT. Cahaya Bintang Medan Tbk and descriptive method. The results showed that the use of Indonesian in the financial statements has met the standards of good and correct language. However, there are still some problems that are less clear to non-accountant readers. For this reason, improvements are needed in the preparation of financial statements, such as the inclusion of additional explanations for accounting terms, to ensure that financial information of a company can be understood by all interested parties.